Molecular docking analysis of RN18 and VEC5 in A3G-Vif inhibition - Sinha, Chanda (Bioinformation, 2014)
The HIV-1 protein Vif is essential for in vivo viral replication that targets the human DNA-editing enzyme, APOBEC3G (A3G), which inhibits replication of retroviruses. The Vif-A3G interactions are believed to be important targets for antiviral drug development. Since the interactions of A3G and Vif evade the ubiquitination pathways in human host, the viral replication precedes which otherwise spreads infection. In this study, two potent Vif inhibitors RN 18 and VEC5 have been evaluated for their inhibitory potential employing ligand receptor and protein-protein interactions studies. VEC 5 showed better interaction with Vif than RN18. Predicted data show that VEC5 bound Vif and RN18 bound Vif showed diminished interaction to A3G compared to inhibitor unbound Vif. However, this should be further validated using in vitro studies.